EXCHANGE AND EXPORT ANALYSIS OF THE COMBINED STOCK PRICE INDEX IN INDONESIA PERIOD 1986-2022 - Meutia Muadzah; Irwan Safwadi; Jariah Abubakar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Many previous studies have proven that there is an influence between the exchange rate (the Rupiah exchange rate against the US Dollar), Exports on the Composite Stock Price Index (IHSG). By using the Autoregressive Distributed Lag (ARDL) model approach using the Eviews 10 program. In this study, we look more deeply at the dynamics of long-term and short-term relationships for the variable exchange rate of the Rupiah against the US Dollar, Exports and the JCI. The research period starts from 1986 to 2022, during which time there are many global upheavals that have a significant impact on Indonesia, one of which is the weakening of the Rupiah exchange rate against the US Dollar. In this study, through the ARDL model of the Rupiah exchange rate against the US Dollar, Exports and JCI are proven to have long-term cointegration or move together in the long term. But not only in the long term, these three variables also have short-term relationship dynamics which have a fairly high speed of adjustment towards balance every year.